RETRACTED: Spectroscopic and molecular modeling studies of binding interaction between the new complex of yttrium and 1,10-phenanthroline derivatives with DNA and BSA - Khorshidi, Mahsa; Asadpour, Saeid; Aramesh-Boroujeni, Zahra; Kooravand, Masoumeh; Mobini Dehkordi, Maryam (Frontiers in Chemistry, 2023)
In this study, 4,9 diazafluoren-9 one ligand and [Y(Daf)2Cl3.OH2] complex was synthesized. The interaction of this complex with DNA and BSA was investigated by UV-Vis and fluorescence spectroscopy. The molecular docking method was used to confirm the experimental results, investigate the type of interaction and determine the binding site. The binding constant and Stern-Volmer constant were calculated using spectroscopy techniques. The binding constant of Y-complex with DNA and BSA was obtained as 1.61×105 M-1 and 0.49×105 M-1, respectively (UV-Vis technique). This parameter was 3.39×105 M-1 and 3.63×105 M-1 for the fluorescence method. The results of experimental and theoretical data showed that the interaction between the yttrium complex with DNA and BSA is the hydrogen bond and van der Waals interaction. This complex communicates DNA with groove interaction. This complex has high binding energy with bovine serum albumin. In addition, the molecular docking results showed that the complex is placed in the IIA subdomain of BSA (site I). Finally, the yttrium complex anticancer activity examined on MCF-7 and A-549 cell lines was studied by the MTT method. The values obtained IC50 showed that the yttrium complex has anti-cancer activity.